Filling the Gaps in Broken Memory while Renewing the Cityscape: Navigating Belonging in Orhan Pamuk’s The Red-Haired Woman - Yılmaz, Simge (Text Matters: A Journal of Literature, Theory and Culture, 2024)
The Red-Haired Woman, one of Orhan Pamuk’s post-Nobel novels, is a concise, fable-like narrative that delves into the complexities of father-son conflicts. The novel parallels the journey of the protagonist, Cem, with the broader socio-cultural context of modern Turkey. It highlights Cem’s struggle between two ideologically contrasting father figures and draws a compelling analogy between his fragmented memory and Turkey’s cultural memories influenced by both the East and West. This paper explores the application of various memory types in the novel, scrutinizes the reliability of its narrators, and analyzes the depiction of urban space in relation to both individual and national memory, with particular focus on the contractor protagonist.